Evaluation of postpartum carbohydrate intolerance and cardiovascular risk factors in women with gestational diabetes - Akinci, Baris; Celtik, Aygul; Genc, Sinan; Yener, Serkan; Demir, Tevfik; Secil, Mustafa; Kebapcilar, Levent; Yesil, Sena (Gynecological endocrinology, 2011)
We aimed to evaluate the predictors of subsequent development of postpartum carbohydrate intolerance, metabolic syndrome and cardiovascular risk factors in women with previous GDM. Two hundred fifty-two consecutive women with GDM were enrolled. After exclusion of women who did not attend to the hospital for follow-up visits for minimum 1 year, data of 195 patients were evaluated. Seventy-one lean women with negative screening for GDM were included as a control group. The prevalence of diabetes, impaired glucose tolerance and impaired fasting glucose and metabolic syndrome was significantly higher in women with previous GDM than healthy controls. Women with previous GDM were more insulin resistant, had an atherogenic lipid profile and increased carotid IMT. The most important predictors of postpartum diabetes were the need for insulin treatment during index pregnancy and glucose values on antepartum OGTT. Among women with previous GDM, the development of postpartum diabetes and metabolic syndrome was associated with increased carotid IMT. Our data show that women with previous GDM are at high risk for developing carbohydrate intolerance, metabolic syndrome and atherosclerosis. Antepartum prediction of high risk subjects for the subsequent development of postpartum carbohydrate intolerance and metabolic syndrome seems to be vital to prevent cardiovascular outcomes.